2017
DOI: 10.1111/vco.12371
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor expression in canine mammary gland and relationship with clinicopathological parameters and progesterone/oestrogen receptors

Abstract: The vitamin D receptor (VDR) belongs to the nuclear class II receptor family. VDR is a ligand transcription factor and mediates the actions of calcitriol, the active product of vitamin D synthesis. Nowadays, it is known that the biological actions of calcitriol include the capacity to modulate cancer features, such as proliferation and differentiation, apoptosis, angiogenesis, invasion and metastasis. VDR expression has been demonstrated in human breast cancer and vitamin D has emerged as a promising targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
5
1
1
Order By: Relevance
“…47 In our study, age was not correlated with serum 25(OH)D and VDBP concentrations in healthy dogs (data not shown), and it is unlikely that the results were affected by age. Although the influence of age on VDR expression in the parathyroid glands of humans 48 and mammary glands in female dogs has been reported, 49 age and serum VDR concentrations in healthy dogs were not correlated in our study (data not shown). Third, we could not evaluate some factors that regulate calcium homeostasis, such as calcitonin and magnesium.…”
Section: Comparison Of Serum 25(oh)d Vdr and Vdbp Concentrations Betw...contrasting
confidence: 73%
“…47 In our study, age was not correlated with serum 25(OH)D and VDBP concentrations in healthy dogs (data not shown), and it is unlikely that the results were affected by age. Although the influence of age on VDR expression in the parathyroid glands of humans 48 and mammary glands in female dogs has been reported, 49 age and serum VDR concentrations in healthy dogs were not correlated in our study (data not shown). Third, we could not evaluate some factors that regulate calcium homeostasis, such as calcitonin and magnesium.…”
Section: Comparison Of Serum 25(oh)d Vdr and Vdbp Concentrations Betw...contrasting
confidence: 73%
“…VDR is the intracellular receptor for VD3, a steroid hormone receptor that is essential for normal mammary gland development (22). Recent studies have shown that VD3 can induce apoptosis, block cell cycle, and inhibit tumor cell proliferation through its receptor VDR in many ways (23)(24)(25). In wild type cells, low dose of VD3 could induce G0/G1 cycle arrest and apoptosis, while VDR knockout cells did not produce cell cycle arrest and apoptosis even under the action of high dose of VD3.…”
Section: Discussionmentioning
confidence: 99%
“…На сьогоднішній день кількість знайдених SNP у VDR перевалює за 400, однак, кореляційний зв'язок із раком молочної залози було знайдено у поліморфізмів FokI (rs2228570), BsmI (rs1544410), TaqI (rs731236), та ApaI (rs7975232) [31,35].…”
Section: результати обговоренняunclassified